Flexible single-crystalline GaN substrate by direct deposition of III-N thin films on polycrystalline metal tape. Issue 7 (25th January 2021) - Shervin, Shahab; Moradnia, Mina; Alam, Md Kamrul; Tong, Tain; Ji, Mi-Hee; Chen, Jie; Pouladi, Sara; Detchprohm, Theeradetch; Forrest, Rebecca; Bao, Jiming; Dupuis, Russell D.; Ryou, Jae-Hyun
Abstract : Demonstration of a mechanically flexible single-crystalline GaN substrate by direct epitaxial growth on metal foil with significantly reduced processing costs and versatile functionality on flexible electronics and photonics. Abstract : Flexible electronics and mechanically bendable devices based on Group III-N semiconductor materials are emerging; however, there are several challenges in manufacturing, such as cost reduction, device stability and flexibility, and device-performance improvement. To overcome these limitations, it is necessary to replace the brittle and expensive semiconductor wafers with single-crystalline flexible templates for a new-bandgap semiconductor platform. The substrates in the new concept of semiconductor materials have a hybrid structure consisting of a single-crystalline III-N thin film on a flexible metal tape substrate which provides a convenient and scalable roll-to-roll deposition process. We present a detailed study of a unique and simple direct epitaxial growth technique for crystallinity transformation to deliver single-crystalline GaN thin film with highly oriented grains along both a -axis and c -axis directions on a flexible and polycrystalline copper tape. A 2-dimensional (2D) graphene having the same atomic configuration as the (0001) basal plane of wurtzite structure is employed as a seed layer which plays a key role in following the III-N epitaxy growth. The DC reactive magnetron sputtering method is then applied to deposit an AlN layer under optimized conditions to achieve preferred-orientation growth. Finally, single-crystalline GaN layers (∼1 μm) are epitaxially grown using metal organic chemical vapor deposition (MOCVD) on the biaxially-textured buffer layer. The flexible single-crystalline GaN film obtained using this method provides a new way for a wide-bandgap semiconductor platform pursuing flexible, high-performance, and versatile device technology.